A molecular reappraisal of matrix-producing breast metaplastic carcinoma highlighted by PLAG1 and MYC rearrangements. Issue 2 (April 2023) - Salvatori, Rebecca; Manzoni, Marco; Lepanto, Daniela; Stufano, Viviana; Pessina, Simona; Zanetti, Chiara; Bassi, Fabio; Mazzarol, Giovanni; Montagna, Emilia; Maffini, Fausto
Background: Very little is currently known about molecular alteration of matrix-producing carcinoma of the breast. However, the morphological similarity with other neoplasm with a myxo-chondroid component is remarkable. In this pilot study we evaluated the molecular alterations involving PLAG1 and MYC genes in 12 cases of matrix producing carcinoma. Methods: We evaluated PLAG1 rearrangements as Break-Apart and Gene Copy Gain, and MYC as amplification and polysomy in 12 cases of matrix producing carcinoma using a FISH method. Results: Among the 12 cases of matrix producing carcinomas we found that the three cases harboring MYC amplification were all negative for PLAG1 break-apart; four cases with MYC polysomy were associated to PLAG1 break-apart and high Gene Copy Number; among four cases wild type for MYC, three showed a PLAG1 - break-apart signal and of them two died with disease. One of the deceased patients showed an amplification of MYC with PLAG1 - wild-type and the other showed a PLAG1 break-apart (6%) and a MYC wild-type. Conclusion: This is the first report to the best of our knowledge that shows a possible correlation between a matrix producing carcinoma with PLAG1 and MYC involvement in the development and progression of this kind of tumor. We can suppose that MYC amplification behaves in an aggressive way together with PLAG1- break-apart in the cases of matrix producing carcinoma presented here. The gene copy gain is a useful diagnostic tool in the case of difficult diagnosis because an increase was observed in more than 50% of cases.